Role of farm-level diversification in the adoption of modern technology in Brazil - Nerlove, Marc; Vosti, Stephen A.; Basel, Wesley (International Food Policy Research Institute, 1996)
The success of modern technology in increasing yields on high-potential lands has been so great that researchers and policymakers alike have been quick to use modern inputs on marginal lands as well. But the results of applying Green Revolution technologies to marginal lands have often been disappointing. What changes in policy and technologies are necessary for use of modern technology to increase the productivity of these marginal lands effectively and sustainably? Research indicates that farms that had substantial yield increases were those that specialized in a few farm products, usually in the products where technological advances were most pronounced. Roles of Farm-Level Diversification in the Adoption of Modern Technology in Brazil, Research Report 104, by Marc Nerlove, Stephen Vosti, and Wesley Basel, focuses on the links between technology adoption and farmers' decisions on product mix and output diversification--on what crops or livestock to produce and in what proportions. The report asks the following questions: Does the production of certain types or combinations of products promote or inhibit the use of modern technology? Does concentration on particular products reduce or increase modern input use? Are farmers who have radically altered their product mix more likely to use modern technology intensively?